Simple and straight forward synthesis of 2,4-disubstituted quinazolines in aqueous medium - Bandaru, Madhav; Sabbavarapu, Narayana Murthy; Pavan, Anil Kumar Bandam Santosh; Akula, Ashwan Kumar; Durga, Nageswar Yadavalli Venkata (European Journal of Chemistry, 2012)
Efficient synthesis of diverse quinazolines from readily available starting materials was achieved in aqueous medium via one-pot protocol. A number of 2,4-disubstituted quinazolines were prepared in moderate to good yields under mild and catalyst-free conditions. Neutral reaction conditions, easy work-up procedures with wide substrate scope and atom economy are the remarkable features of this method.